A Review of the Emerging Field of Underwater Mass Spectrometry - Chua, Emily J.; Savidge, William; Short, R. Timothy; Cardenas-Valencia, Andres M.; Fulweiler, Robinson W. (Frontiers in Marine Science, 2016)
Mass spectrometers are versatile sensor systems, owing to their high sensitivity and ability to simultaneously measure multiple chemical species. Over the last two decades, traditional laboratory-based membrane inlet mass spectrometers have been adapted for underwater use. Underwater mass spectrometry has drastically improved our capability to monitor a broad suite of gaseous compounds (e.g., dissolved atmospheric gases, light hydrocarbons, and volatile organic compounds) in the aquatic environment. Here we provide an overview of the progress made in the field of underwater mass spectrometry since its inception in the 1990s to the present. In particular, we discuss the approaches undertaken by various research groups in developing in situ mass spectrometers. We also provide examples to illustrate how underwater mass spectrometers have been used in the field. Finally, we present future trends in the field of in situ mass spectrometry. Most of these efforts are aimed at improving the quality and spatial and temporal scales of chemical measurements in the ocean. By providing up-to-date information on underwater mass spectrometry, this review offers guidance for researchers interested in adapting this technology as well as goals for future progress in the field.